(untitled) (Physical Education, Health and Social Sciences, 2025)
We explored the impact of different diets on the growth and health of newly hatched chicks. Our experiment involved four groups that are consisting of 2 chicks, each group receiving unique diet: Pearl Millet, Pearl Millet and whole wheat bread, Pearl Millet and apple and commercial chicks’ feed. Over a seven-day period, we clearly monitored the chick’s progress thoroughly and observed a prominent change in their weight gain during the whole period of research. Our findings revealed that the groups fed Pearl Millet, Pearl Millet and Whole wheat bread and Pearl Millet and Apple experienced one mortality each, while chicks receiving commercial chicks feed thrived. This research underscores the significance of balanced nutrition for young chicks and highlights the varying effects of different diets on their development. We gained very postive results with few mortalities rate. The highest impact on nutrition was of commercial chick feed, which shows it contain all nutrients essential for a chick to develop. For a healthy and quick growth of chicks in short time and limited resources commercial chick best is the best options for the breeders in poultry farm or people who are fond of chicks as pet. Quick growth and good health with maximum survival ratio will ultimately benefit financially to respective persons. Our Research can be very beneficial for those who are finding best way to increase their poultry farm chick’s number.